Skeletal muscle interleukin‐6 regulates metabolic factors in iWAT during HFD and exercise training. (22nd June 2015) - Knudsen, Jakob G.; Bertholdt, Lærke; Joensen, Ella; Lassen, Signe B.; Hidalgo, Juan; Pilegaard, Henriette
<x xml:space="preserve">Abstract</x> Objective To investigate the role of skeletal muscle (SkM) interleukin (IL)‐6 in the regulation of adipose tissue metabolism. Methods Muscle‐specific IL‐6 knockout (IL‐6 MKO) and IL‐6loxP/loxP (Floxed) mice were subjected to standard rodent diet (Chow), high‐fat diet (HFD), or HFD in combination with exercise training (HFD ExTr) for 16 weeks. Results Total fat mass increased (P < 0.05) in both genotypes with HFD. However, HFD IL‐6 MKO mice had lower (P < 0.05) inguinal adipose tissue (iWAT) mass than HFD Floxed mice. Accordingly, iWAT glucose transporter 4 (GLUT4) protein content, 5′AMP activated protein kinase (AMPK)Thr172 phosphorylation, and fatty acid synthase (FAS) mRNA content were lower (P < 0.05) in IL‐6 MKO than Floxed mice on Chow. In addition, iWAT AMPKThr172 and hormone‐sensitive lipase (HSL)Ser565 phosphorylation as well as perilipin protein content was higher (P < 0.05) in HFD IL‐6 MKO than HFD Floxed mice, and pyruvate dehydrogenase E1α (PDH‐E1α) protein content was higher (P < 0.05) in HFD ExTr IL‐6 MKO than HFD ExTr Floxed mice. Conclusions These findings indicate that SkM IL‐6 affects iWAT mass through regulation of glucose uptake capacity as well as lipogenic and lipolytic factors.